Life History of Epuraea (Haptoncus) ocularis Fairmaire, 1849 in Kolkata area, India and descriptions of the immature stages (Coleoptera: Nitidulidae: Epuraeinae) - Dasgupta, J.; Pal, T. K. (Zootaxa, 2021)
Sap beetle, Epuraea ocularis Fairmaire usually lays eggs and breeds on fermenting overripe fruits, and larvae pass through different instars before pupating on soil. In laboratory condition, mating pairs of adults copulated and females laid eggs in clusters; larva hatched out in 1 to 2 days, passed through four instars; mature larva migrated to soil for pupation. Larval development took about 12 to 17 days; and adult hatched out of pupa in about 4 to 5 days. Detailed morphology of egg, larva and pupa is presented herein, and significance of larva in taxonomy of beetles has been indicated.